ABOUT EVIDENCE-BASED NURSING: SOME QUESTIONS, LIMITATIONS AND RECOMMENDATIONS TO ITS IMPLEMENTATION - Ochoa Marín, Sandra Catalina (Investigación y Educación en Enfermería, 2008)
<!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Presently the focus of nursing professional’s efforts toward the consolidation of a base of concrete knowledge that facilitates the continuous development of nursing as a scientific discipline and a recognized one. To reach this goal it is fundamental to ensure evidence-based practice provided by research findings in both clinic and community settings, as well as in advocacy and education. This paper is a reflection on the need of nursing professional’s commitment to the development of the discipline through the improvement of research. These needs to be prudent incorporation of work methodologies based on theoretical debate and evidence of best practice in nursing. Furthermore, this paper shows findings, limitations, criticism and some recommendations to the implementation of evidence-based nursing in the sphere of adult health care as a strategy to improve and strengthen professional practice.